Mutace BRAF: nový přístup k cílené léčbě melanomu - Arenbergerová, M; Puzanov, I (Klinicka onkologie, 2012)
The incidence of malignant melanoma is increasing worldwide, despite our best efforts in prevention and early detection. The locally advanced disease may be treated surgically with good results, however, metastatic melanoma is considered to be one of the most therapeutically challenging malignancies. The increasing knowledge of molecular changes in melanoma may change this picture. Malignant melanoma is not a singular, homogeneous disease but rather a mixture of subtypes characterized by specific mutations. Tumors with C-KIT mutation respond to therapy with C-KIT kinase inhibitor imatinib and the ones characterized by BRAF mutations respond to BRAF kinase inhibitor vemurafenib. Vemurafenib was approved by US FDA in 2011 and EMA in 2012 for therapy of patients with advanced melanoma, harboring mutation in BRAFV600E gene. Ipilimumab, an antibody to cytotoxic T-lymphocyte antigen 4 (CTLA-4), was registered in 2011 by both US FDA and European Medicines Agency for treatment of metastatic melanoma. This therapy promotes the anti-tumor T-cell activity by blocking a CTLA-4 antigen, a key negative regulator of immune response.
Keywords: indoly; nádory kůže; Humans; Skin Neoplasms; Indoles; Proto-Oncogene Proteins B-raf; melanom; Molecular Targeted Therapy; mutace; sulfonamidy; protokoly protinádorové kombinované chemoterapie; lidé; vemurafenib; Phosphatidylethanolamine Binding Protein; protoonkogenní proteiny B-Raf; Melanoma; Vemurafenib; Antineoplastic Combined Chemotherapy Protocols; cílená molekulární terapie; Mutation; Sulfonamides; protein vázající fosfatidylethanolamin